Rola i zadania ksieni według Reguły św. Donata - Czyżewski, Bogdan Stanisław (Vox Patrum, 2025)
St. Donatus (590/596–670), author of the Rule for virgins living in the Gaul monastery Joussa-Moutier (Jussanum monasterium), belonged to eminent figures of the early Church. He was Bishop of Besançon (Vesontium) in Gallia, participant in three important church synods and also founder of the monastery of Saint Paul. His Rule is not an original work but a compilation of three known rules written by of St. Benedict, St. Caesarius of Arles and St. Columbanus. Despite this, it is worth getting acquainted with it to be convinced that based on elements of three works, Donatus was able to write a good rule, adapted to a women’s convent both in terms of provisions and vocabulary referring to women. The legislator devoted much space to the abbess (abbatissa), the equivalent of the abbot (abbas) in a men’s community. She was to have exceptional spiritual and moral qualities, know the Holy Scriptures, observe the Rule, be a true mother to the nuns, able to admonish and rebuke them with love, make demands and love them, and above all, be aware of her responsibility before God for all decisions made in the abbey.